PENGEMBANGAN ATTITUDE E-ASSESSMENT PADA PEMBELAJARAN MATEMATIKA SEKOLAH MENENGAH ATAS - Permadi, Teguh; Mustangin, Mustangin (JPM : Jurnal Pendidikan Matematika, 2015)
Mathematics has important roles in forming the students' character at school. At least, there are nine characters' value which can be formed through learning mathematics, there are:religious, disciplined, honest, hard working, creative, curiosity, independent, communicative, and responsibility. Therefore, teachers need a means to assess those characters. Technology can be used as a means or tool in the assessment of learning, this term is referred as e-assessment. Originating from an idea for combining between assessing the attitude and using the e-assessment, the researcher developed the attitude e-assessment. The purpose of this research is to produce the attitude e-assessment in teaching Mathematics at high school. This study is a part of developing research which used 4D model as the development basis that cover define stages, design, develop, and disseminate. The result of the analysis which is conducted to the practitioners, learning evaluation expert, and instructional media expert, the product of e-assessment got 3,34 which means that it is valid. While the analysis result of users' respond which is conducted to 10 students grade X of Madrasah Aliyah Negeri Kota Batu, the e-assessment product got 3,32 which means that its valid.Based onthose tests, theattitudee-assessmentproducts in thehigh schoolmathematicsteachinghas been declaredvalidorproper.